(untitled) (Journal of Informatics Education and Research, 2024)
The integration of Environmental, Social and Governance (ESG) principles into business education represents a paradigm shift in preparing business leaders for a sustainable and responsible global economy. This research paper presents the process of introducing the ESG Modular Specialization while incorporating ESG concepts in the Post Graduate Diploma in Management (PGDM) curriculum at a premium business school based in south India. The study discusses the motivations and the experiences behind the adoption of ESG in the curriculum, the methods of integration, the challenges faced, and the experiences. The authors shared the effect on students’ knowledge, attitudes, and skills. The research paper intends to discuss the broader implications of curriculum transformation for business education and the corporate world.